2021
DOI: 10.1099/ijsem.0.004558
|View full text |Cite
|
Sign up to set email alerts
|

Algibacillus agarilyticus gen. nov., sp. nov., isolated from the surface of the red algae Gelidium amansii

Abstract: A novel Gram-stain-negative, strictly aerobic, coccoid and agar-hydrolysing bacterium, designated RQJ05T, was isolated from the marine red algae Gelidium amansii collected from the coastal area of Rizhao, PR China. Cells of strain RQJ05T were approximately 0.8–1.0×1.3–3.0 µm in size and motile by means of a polar flagellum. Growth occurred at 4–33 °C (optimum, 25–30 °C), pH 7.0–8.5 (optimum, pH 7.5–8.0) and in the presence of 1.0–7.0 % (w/v) NaCl (optimum, 2.0–3.0 %). Strain RQJ05T showed oxidase-positive and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The genome analysis revealed that the type strain A. agarilyticus RQJ05 T also possessed three β-agarases [7]. In 2019, Lau and colleagues isolated an agarolytic bacterium, a Catenovulum -like strain designated as CCB-QB4 T , from a coastal area of Penang, Malaysia (5° 19′ 30″ N; 100° 18′ 12″ E), and its complete genome was studied [8].…”
Section: Full-textmentioning
confidence: 99%
See 4 more Smart Citations
“…The genome analysis revealed that the type strain A. agarilyticus RQJ05 T also possessed three β-agarases [7]. In 2019, Lau and colleagues isolated an agarolytic bacterium, a Catenovulum -like strain designated as CCB-QB4 T , from a coastal area of Penang, Malaysia (5° 19′ 30″ N; 100° 18′ 12″ E), and its complete genome was studied [8].…”
Section: Full-textmentioning
confidence: 99%
“…In contrast, A. agarilyticus RQJ05 T could grow in MB without supplementation of carbon sources [7]. All these five strains exhibited positive reactions for oxidase, alkaline phosphatase and naphthol-AS-BI-phosphohydrolase enzyme activities and were capable of starch and agar hydrolysis .…”
Section: Full-textmentioning
confidence: 99%
See 3 more Smart Citations